A new species of the genus Leptolalax (Anura: Megophryidae) from Mt. Gaoligongshan of western Yunnan Province, China - Yang, Jian-Huan; Wang, Ying-Yong; Chen, Guo-Ling; Rao, Ding-Qi (Zootaxa, 2016)
A new species of the genus Leptolalax is described from the Tengchong Section of Gaoligongshan National Nature Reserve, Tengchong County, Yunnan Province, China. The new species, Leptolalax tengchongensis sp. nov., can be distinguished from its congeners by a combination of the following characters: (1) small size (SVL 23.9–26.0 mm in males, 28.8–28.9 mm in females); (2) dorsal skin shagreened and scattered with fine, round reddish tubercles; (3) toes with rudimentary webbing and narrow lateral fringes; (4) tympanum distinctly discernible, almost entirely black; (5) ventrolateral glands indistinct; (6) flanks with several distinct and large dark blotches; (7) ventral surfaces white, scattered with distinct irregular dark speckling; (8) iris not bicolored, uniformly dark brown and scattered with minute, coppery reticulations throughout. To date, the new species has only been found at its type locality in evergreen broadleaf forests at elevations between 2000–2100 m.